The dictator's screenplay: collective memory narratives and the legitimacy of communist rule in East Asia. Issue 4 (19th May 2021) - Hellmann, Olli
ABSTRACT: Through a carefully crafted comparison of East Asia's surviving communist regimes (North Korea, China, Vietnam, Laos), this article offers a rare systematic study of how dictatorships manipulate collective memory to their own advantage. I employ methods of narrative analysis to identify different storytelling strategies that may serve to anthropomorphize the regime party as the "hero" in relation to the historical past. Moreover, I rely on quantitative content analysis ( N  > 2000) to demonstrate that the four communist regimes use propaganda photographs of their respective leaders to communicate collective memory narratives to mass audiences. The article thus makes two original contributions to the literature on autocratic politics. First, I show that narratives provide autocratic regimes with a powerful tool to tap into different sources of legitimacy, including output and identity legitimacy. Second, the findings of the visual content analysis suggest that, contrary to existing views, personalization – at least in terms of media personalization – does not have to come at the expense of the regime party.